1180MPa-grade hot-dip galvanized high-strength steel and preparation method thereof

By rationally designing the chemical composition and microstructure of the steel, using the phase change inducing plastic effects and the ability to suppress cracks, the problem of insufficient elongation of 1180MPa grade hot-dip galvanized high-strength steel is solved, and high elongation and excellent mechanical properties are achieved, which is suitable for the formation of complex parts in the automobile industry.

CN119876763APending Publication Date: 2025-04-25SHOUGANG GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510119674.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing 1180MPa grade hot-dip galvanized high-strength steel is difficult to achieve high elongation and cannot meet the automotive industry's demand for high elongation and forming performance.

Method used

By rationally designing the chemical composition of the steel, we ensure that the microstructure of the steel matrix contains high volume fraction residual austenite, and use slat-shaped ferrite + martensite + paralympic tissue to use the phase change to induce plastic effects and the ability to inhibit cracks to improve the elongation of the material.

Benefits of technology

The high elongation of 1180MPa grade hot-dip galvanized high-strength steel is achieved, with an elongation of A80≥13%, while ensuring the yield strength ≥850MPa and the tensile strength ≥1180MPa, which is suitable for the forming needs of complex parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876763A_ABST
    Figure CN119876763A_ABST
Patent Text Reader

Abstract

The invention provides 1180MPa-grade hot-dip galvanized high-strength steel and a preparation method thereof, and belongs to the field of steel preparation. The steel matrix comprises the following chemical components in percentage by mass: 0.23%-0.28% of C, 1.0%-1.9% of Si, 2.3%-2.8% of Mn and the balance of Algt; 0 and < = 0.1%, P < = 0.02%, S < = 0.01%, Nbgt; 0 and less than or equal to 0.04%, Tigt; 0 < = 0.04%, and the balance Fe and inevitable impurities. The chemical components of the steel are reasonably designed, so that the structure contains retained austenite with high volume fraction, and the transformation induced plasticity effect can be continuously generated in the deformation process, so that the plasticity of the material is effectively improved; meanwhile, the structure is composed of lath-shaped ferrite, martensite and residual austenite, and the lath-shaped structure has the higher capacity of restraining crack initiation and expansion. Therefore, the ductility of the hot-dip galvanized high-strength steel is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of steel preparation, and in particular to a 1180MPa grade hot-dip galvanized high-strength steel and a preparation method thereof. Background Art

[0002] With the continuous increase in automobile production and ownership, while bringing convenience to people's travel and driving economic growth, it also causes problems such as environmental pollution. Lightweighting of automobiles is the most direct and effective means to reduce automobile fuel consumption and emissions. Experiments and studies have shown that for every 10% decrease in the dead weight of a passenger car, its fuel consumption and emissions will decrease by 6% to 8%. For new energy vehicles, lightweighting is even more important due to the weight gain of batteries and the limitations of battery power ratio. In order to meet the increasingly stringent safety regulations continuously issued by governments of various countries, while lightweighting automobiles, improving safety has become an inevitable trend in the development of the automobile industry. High-strength steel and advanced high-strength steel are modern automobile manufacturing materials with high cost performance that can ensure both lightweighting of automobiles and improving and ensuring automobile safety.

[0003] At the same time, the automotive industry has an increasingly urgent need for high-strength steel with higher elongation and formability. The new standard of the German Association of the Automotive Industry (VDA) proposes the concept of high-elongation FH steel. Its 1180MPa grade FH steel requires A 80 Greater than 13%, but the 1180MPa high-strength steel produced by the current conventional galvanizing process is difficult to meet this requirement. Summary of the invention

[0004] The present application provides a 1180MPa grade hot-dip galvanized high-strength steel and a preparation method to solve the following technical problem: how to improve the elongation of 1180MPa grade hot-dip galvanized high-strength steel.

[0005] In a first aspect, the present application provides a 1180MPa grade hot-dip galvanized high-strength steel, the hot-dip galvanized high-strength steel comprising a steel substrate and a galvanized layer attached to at least a portion of the surface of the steel substrate, wherein the chemical composition of the steel substrate comprises, by mass fraction: C: 0.23% to 0.28%, Si: 1.0% to 1.9%, Mn: 2.3% to 2.8%, Al>0 and ≤0.1%, P≤0.02%, S≤0.01%, Nb>0 and ≤0.04%, Ti>0 and ≤0.04%, and the remainder is Fe and unavoidable impurities;

[0006] Measured by volume fraction, the microstructure of the steel matrix includes: ferrite: 10% to 30%, martensite: 75% to 85%, and retained austenite: 9% to 18%.

[0007] Optionally, the microstructures of the ferrite, martensite and retained austenite are all lath-shaped.

[0008] Optionally, the average grain size of the ferrite is ≤3 μm, the average grain size of the martensite is ≤1.5 μm, and the average grain size of the retained austenite is ≤0.8 μm.

[0009] Optionally, the chemical composition of the steel matrix includes, by mass fraction: C: 0.24% to 0.26%, Si: 1.4% to 1.7%, Mn: 2.4% to 2.6%, Nb: 0.01% to 0.03%, and Ti: 0.01% to 0.03%.

[0010] Optionally, the hot-dip galvanized high-strength steel meets at least one of the following properties: yield strength ≥850MPa, tensile strength ≥1180MPa, elongation A80 ≥13%, and hole expansion rate ≥32%.

[0011] In a second aspect, the present application provides a method for preparing the hot-dip galvanized high-strength steel according to any one embodiment of the first aspect, the method comprising:

[0012] Obtaining a casting billet having the chemical composition;

[0013] The ingot is heated, rolled, cooled and coiled in sequence to obtain a hot-rolled plate; the coiling temperature is ≤300°C;

[0014] The hot-rolled plate is subjected to surface treatment to obtain a steel matrix;

[0015] The steel substrate is subjected to continuous hot-dip galvanizing annealing to obtain hot-dip galvanized high-strength steel.

[0016] Optionally, the steel substrate is subjected to continuous hot-dip galvanizing annealing to obtain hot-dip galvanized high-strength steel, comprising:

[0017] The steel substrate is subjected to a soaking treatment at a temperature of 750° C. to 850° C.;

[0018] Slowly cooling the steel substrate after the soaking treatment; the slow cooling temperature is 650° C. to 720° C.;

[0019] The steel substrate is rapidly cooled after slow cooling; the rapid cooling temperature is 150° C. to 250° C.;

[0020] Performing aging treatment on the steel matrix after rapid cooling;

[0021] The steel substrate after aging treatment is hot-dip galvanized to obtain hot-dip galvanized high-strength steel.

[0022] Optionally, the temperature of the aging treatment is 200° C. to 350° C., and the time of the aging treatment is 0.5 min to 1 min.

[0023] Optionally, the hot dip coating temperature is 440°C to 460°C, and the hot dip coating belt speed is 70mpm to 100mpm.

[0024] Optionally, the heating temperature is 1150°C to 1250°C; and / or the final rolling temperature is 870°C to 930°C; and / or the coiling temperature is 200°C to 300°C.

[0025] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0026] The present application provides a 1180MPa grade hot-dip galvanized high-strength steel, which includes a steel substrate and a galvanized layer attached to at least a portion of the surface of the steel substrate. The chemical composition of the steel substrate includes, by mass fraction, C: 0.23% to 0.28%, Si: 1.0% to 1.9%, Mn: 2.3% to 2.8%, Al>0 and ≤0.1%, P≤0.02%, S≤0.01%, Nb>0 and ≤0.04%, Ti>0 and ≤0.04%, and the remainder is Fe and unavoidable impurities; by volume fraction, the microstructure of the steel substrate includes: ferrite: 10% to 30%, martensite: 75% to 85%, and retained austenite: 9% to 18%. The chemical composition of the steel is reasonably designed, so that the organization contains a high volume fraction of residual austenite, which can continuously produce phase transformation induced plasticity effect during deformation, thereby effectively improving the plasticity of the material; at the same time, the organization is composed of lath-shaped ferrite + martensite + residual austenite, and the lath-shaped organization has a stronger ability to inhibit crack initiation and expansion. Under the combined effect of these two factors, the 1180MPa grade hot-dip galvanized high-strength steel has extremely high elongation, which can meet the needs of complex parts forming. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0028] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0029] Figure 1 A schematic flow chart of a method for preparing 1180MPa grade hot-dip galvanized high-strength steel provided in an embodiment of the present application;

[0030] Figure 2 The microstructure of the 1180MPa grade hot-dip galvanized high-strength steel provided in Example 1 of the present application;

[0031] Figure 3 This is a typical microstructure of the conventional 1180MPa grade hot-dip galvanized dual-phase steel provided in this application. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0033] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0034] In addition, in the description of the specification of the present application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "the following at least one item (items)" or similar expressions refer to any combination of these items, including any combination of single items (items) or plural items (items). For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or plural, respectively.

[0035] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0036] In a first aspect, the present application provides a 1180MPa grade hot-dip galvanized high-strength steel, the hot-dip galvanized high-strength steel comprising a steel substrate and a galvanized layer attached to at least a portion of the surface of the steel substrate, wherein the chemical composition of the steel substrate comprises, by mass fraction: C: 0.23% to 0.28%, Si: 1.0% to 1.9%, Mn: 2.3% to 2.8%, Al>0 and ≤0.1%, P≤0.02%, S≤0.01%, Nb>0 and ≤0.04%, Ti>0 and ≤0.04%, and the remainder is Fe and unavoidable impurities;

[0037] Measured by volume fraction, the microstructure of the steel matrix includes: ferrite: 10% to 30%, martensite: 75% to 85%, and retained austenite: 9% to 18%.

[0038] The positive effects of controlling the C content to 0.23% to 0.28% are as follows: C is the main interstitial solid solution strengthening element, which can improve the hardenability of the material and is conducive to obtaining the martensitic hard phase. It is also the main austenite stabilizing element, which is conducive to obtaining a large amount of highly stable residual austenite; too low a C content can easily lead to insufficient strength, and too high a C content can easily lead to embrittlement of the material. Exemplarily, the C content is 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, etc.

[0039] The positive effect of controlling the Si content to 1.0% to 1.9% is that the main function of Si is to obtain retained austenite with good stability, and it is also the main solid solution strengthening element; too low Si content is not conducive to obtaining a good amount and stability of retained austenite, and too high Si content is not conducive to the surface quality of the strip and the cold rolling process. Exemplary, the Si content is 1.0%, 1.1%, 1.3%, 1.4%, 1.5%, 1.7%, 1.9%, etc.

[0040] The positive effect of controlling the Mn content to 2.3% to 2.8% is that Mn is the main solid solution strengthening element and hardenability element, and is also one of the austenite stabilizing elements; too low a Mn content is not conducive to obtaining the required tensile strength, and too high a Mn content will lead to excessive alloy cost and poor strip surface quality. Exemplarily, the Mn content is 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, etc.

[0041] Positive effects of controlling the Al content to >0 and ≤0.1%: Al has a similar effect to Si in improving the stability of the Paralympic steel, but Al is not conducive to the castability of the ingot, so its content is controlled below 0.1%. For example, the Al content can be 0.01%, 0.03%, 0.04%, 0.05%, 0.07%, 0.09%, 0.1%, etc.

[0042] Positive effects of controlling the P content ≤ 0.02%: P is an inevitable impurity in steel, which is easy to form micro segregation when the molten steel solidifies, and segregates to the grain boundary during the subsequent heat treatment process, which significantly increases the brittleness of the steel. The content should be controlled below 0.02%. Exemplarily, the P content can be 0.005%, 0.008%, 0.01%, 0.012%, 0.015%, 0.018%, 0.02%, etc.

[0043] The positive effect of controlling the S content ≤ 0.01%: S is also an inevitable impurity in steel, which is easy to form MnS inclusions, thereby reducing the toughness and plasticity of steel. The content should be controlled below 0.01%. For example, the S content can be 0.001%, 0.003%, 0.006%, 0.008%, 0.01%, etc.

[0044] The positive effect of controlling the Nb content to >0 and ≤0.04% is that Nb is a typical microalloying element. The solid solution of Nb and the carbonitride formed can refine the grains. Carbonitride can also improve the sensitivity to hydrogen embrittlement. However, too much carbonitride is not good for plasticity. Therefore, the Nb content of this patent is controlled below 0.04%. For example, the Nb content can be 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, etc.

[0045] The positive effect of controlling the Ti content to >0 and ≤0.04% is that Ti is also a typical microalloying element. Ti carbonitride can effectively increase the precipitation strengthening increment and improve hydrogen embrittlement sensitivity. Too much carbonitride is not conducive to improving plasticity. The Nb content of this patent is controlled below 0.04%. For example, the Ti content can be 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, etc.

[0046] In some embodiments, the microstructures of the ferrite, martensite and retained austenite are all lath-shaped.

[0047] The lath-like structure has a stronger ability to inhibit crack initiation and propagation, thereby effectively improving the elongation of hot-dip galvanized high-strength steel.

[0048] In some embodiments, the average grain size of the ferrite is ≤3 μm, the average grain size of the martensite is ≤1.5 μm, and the average grain size of the retained austenite is ≤0.8 μm.

[0049] Through process innovation, the microstructure morphology and phase ratio of high-strength steel are optimized. On the basis of obtaining lath-shaped ferrite + martensite, a high volume fraction (9-18%) of residual austenite is obtained. The high volume fraction of retained austenite can continuously produce the transformation induced plasticity effect (TRIP effect) during the deformation process, thereby effectively improving the plasticity of the material and obtaining excellent elongation, which is suitable for complex drawing and forming automotive structural parts. For example, the volume fraction of ferrite can be 10%, 12%, 15%, 18%, 20%, 25%, 30%, etc., the volume fraction of martensite can be 75%, 77%, 79%, 80%, 82%, 84%, 85%, etc., and the volume fraction of retained austenite can be 9%, 10%, 12%, 14%, 16%, 18%, etc.

[0050] In some embodiments, the chemical composition of the steel matrix includes, by mass fraction: C: 0.24% to 0.26%, Si: 1.4% to 1.7%, Mn: 2.4% to 2.6%, Nb: 0.01% to 0.03%, and Ti: 0.01% to 0.03%.

[0051] In some embodiments, the hot-dip galvanized high-strength steel meets at least one of the following properties: yield strength ≥850 MPa, tensile strength ≥1180 MPa, elongation A80 ≥13%, and hole expansion ratio ≥32%.

[0052] Through process innovation, the microstructure morphology and phase ratio of high-strength steel are optimized. On the basis of obtaining lath-shaped ferrite + martensite, a high volume fraction (9-18%) of residual iron content is obtained, thereby ensuring that the mechanical properties of hot-dip galvanized high-strength steel meet the yield strength ≥850MPa, tensile strength ≥1180MPa, elongation A80 ≥13%, and hole expansion rate ≥32%, which is suitable for complex drawing-formed automotive structural parts. Exemplarily, the yield strength can be 850MPa, 860MPa, 870MPa, 900MPa, 920MPa, 930MPa, etc., the tensile strength can be 1180MPa, 1190MPa, 1200MPa, 1210MPa, 1220MPa, 1230MPa, etc., the elongation A80 can be 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, etc., and the hole expansion rate can be 32%, 32.5%, 33%, 33.5%, 34%, 35%, etc.

[0053] Figure 1 A schematic flow chart of a method for preparing 1180MPa grade hot-dip galvanized high-strength steel provided in an embodiment of the present application.

[0054] See also Figure 1 The present application provides a method for preparing hot-dip galvanized high-strength steel, the method comprising:

[0055] S1, obtaining a casting billet having the chemical composition;

[0056] S2, heating, rolling, cooling and coiling the ingot in sequence to obtain a hot-rolled plate; the coiling temperature is ≤300°C;

[0057] In some embodiments, the heating temperature is 1150°C to 1250°C; and / or the coiling temperature is 200°C to 300°C; and / or the final rolling temperature is 870°C to 930°C.

[0058] The positive effect of controlling the heating temperature to 1150°C to 1250°C is that the homogenization of the structure and the solid solution of the micro-alloying elements can be ensured. Too high a temperature may cause abnormal grain growth, and too low a temperature may cause uneven composition and insufficient solid solution of the micro-alloying elements. Exemplarily, the heating temperature is 1150°C, 1170°C, 1190°C, 1200°C, 1220°C, 1240°C, 1250°C, etc.

[0059] The positive effect of controlling the final rolling temperature of rolling to 870°C to 930°C is to ensure a good hot rolling structure and avoid excessively coarse grains and mixed crystals. Exemplarily, the final rolling temperature of the rolling is 870°C, 880°C, 900°C, 910°C, 920°C, 930°C, etc.

[0060] The positive effect of controlling the coiling temperature to 200°C to 300°C: controlling the coiling temperature to ≤300°C can obtain a full martensite structure. Exemplarily, the coiling temperature can be 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, etc.

[0061] S3, performing surface treatment on the hot-rolled plate to obtain a steel matrix;

[0062] In some embodiments, the surface treatment is pickling, which can remove iron oxide scale on the surface of the steel plate.

[0063] S4. The steel substrate is subjected to continuous hot-dip galvanizing annealing to obtain hot-dip galvanized high-strength steel.

[0064] In some embodiments, the step of subjecting the steel substrate to continuous hot-dip galvanizing annealing to obtain hot-dip galvanized high-strength steel comprises:

[0065] The steel substrate is subjected to a soaking treatment at a temperature of 750° C. to 850° C.;

[0066] Slowly cooling the steel substrate after the soaking treatment; the slow cooling temperature is 650° C. to 720° C.;

[0067] The steel substrate is rapidly cooled after slow cooling; the rapid cooling temperature is 150° C. to 250° C.;

[0068] Performing aging treatment on the steel matrix after rapid cooling;

[0069] The steel substrate after aging treatment is hot-dip galvanized to obtain hot-dip galvanized high-strength steel.

[0070] In some embodiments, the temperature of the aging treatment is 200° C. to 350° C., and the time of the aging treatment is 0.5 min to 1 min.

[0071] In some embodiments, the hot-dip coating temperature is 440° C. to 460° C., and the hot-dip coating belt speed is 70 mpm to 100 mpm.

[0072] The positive effect of controlling the soaking temperature between 750 and 850°C: the soaking temperature is within the two-phase temperature range of the chemical composition of the ingot. If it is too low, it is not conducive to obtaining a sufficient number of stable Paralyzes. If it is too high, the annealing structure loses its lath shape, which is not conducive to improving the Paralyze stability. For example, the soaking temperature can be 750°C, 770°C, 790°C, 800°C, 820°C, 840°C, 850°C, etc.

[0073] The positive effect of controlling the slow cooling temperature to 650°C to 720°C is that the ferrite content can be adjusted. Exemplarily, the slow cooling temperature is 650°C, 670°C, 690°C, 700°C, 710°C, 720°C, etc.

[0074] The positive effects of controlling the rapid cooling temperature to 150℃~250℃ and the aging treatment temperature to 200℃~350℃ are: most of the austenite formed in the two-phase region is transformed into martensite, and an appropriate amount of residual austenite with moderate stability is obtained. A rapid cooling temperature that is too low is not conducive to the improvement of the volume fraction of the Para-Austenite, and a high temperature has an impact on the stability of the Para-Austenite; if the aging temperature is too low, the partitioning effect is not good, and if it is too high, it promotes the precipitation of carbides in austenite, which is not good for the volume fraction and stability of the Para-Austenite. Exemplarily, the rapid cooling temperature can be 150℃, 170℃, 190℃, 200℃, 220℃, 240℃, 250℃, etc. The temperature of the aging treatment can be 200℃, 220℃, 250℃, 280℃, 300℃, 320℃, 350℃, etc.

[0075] The positive effect of controlling the aging treatment time between 0.5 and 1 minute: if it is too short, the distribution effect is not obvious, and if it is too long, the production line investment is too large. For example, the aging treatment time can be 0.5 minutes, 0.6 minutes, 0.7 minutes, 0.8 minutes, 0.9 minutes, 1 minute, etc.

[0076] The hot-dip temperature is the temperature of the strip entering the zinc pot, which is controlled to be 440-460°C, and the belt speed is 70-100 mpm. The positive effect is to improve the quality of the galvanized layer. Exemplarily, the hot-dip temperature is 440°C, 445°C, 450°C, 455°C, 460°C, etc., and the hot-dip belt speed is 70 mpm, 75 mpm, 80 mpm, 90 mpm, 95 mpm, 100 mpm, etc.

[0077] The specific chemical composition and process conditions in the embodiments of the present invention are mainly determined for the development of hot-dip galvanized steel sheets for automobiles, but the concept of the present invention is also applicable to medium and thick plates, profiles, and rods and wires.

[0078] The product prepared by the method for preparing hot-dip galvanized high-strength steel is the above-mentioned hot-dip galvanized high-strength steel. The chemical composition and microstructure of the hot-dip galvanized high-strength steel prepared by the method for preparing hot-dip galvanized high-strength steel can refer to the above-mentioned embodiment. Since the method for preparing hot-dip galvanized high-strength steel adopts part or all of the technical solutions of the hot-dip galvanized high-strength steel embodiment, it at least has all the beneficial effects brought by the technical solutions of the hot-dip galvanized high-strength steel embodiment, which will not be repeated here one by one.

[0079] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.

[0080] The molten steel is smelted in a converter to obtain the chemical composition of the steel matrix of hot-dip galvanized high-strength steel, as shown in Table 1.

[0081] Table 1 Chemical composition of the steel matrix of hot-dip galvanized high-strength steel (wt%), the balance is Fe and unavoidable impurities

[0082] Group C Si Mn Al P S Nb Ti Example 1 0.25 1.5 2.6 0.03 0.010 0.002 0.020 0.018 Comparative Example 1 0.29 1.7 2.6 0.04 0.011 0.002 0.020 0.020 Comparative Example 2 0.21 1.6 2.5 0.03 0.012 0.003 0.020 0.015 Comparative Example 3 0.25 1.6 2.1 0.03 0.009 0.002 0.021 0.016 Comparative Example 4 0.25 0.9 2.6 0.03 0.010 0.002 0.019 0.019 Comparative Example 5 0.25 1.5 2.6 0.03 0.010 0.002 -- 0.020 Comparative Example 6 0.25 1.5 2.6 0.03 0.010 0.002 0.019 -- Comparative Examples 7 to 9 0.25 1.5 2.6 0.03 0.010 0.002 0.020 0.018

[0083] Based on the chemical composition of the steel matrix of the embodiment and the comparative example, this embodiment also provides a method for preparing hot-dip galvanized high-strength steel, comprising the following steps:

[0084] S11, obtaining a casting billet having the chemical composition;

[0085] S21, heating, rolling, cooling and coiling the ingot in sequence to obtain a hot-rolled plate; the heating temperature is 1200° C., the final rolling temperature of the rolling is 900° C., and the coiling temperature is 250° C.;

[0086] S31, pickling the hot-rolled plate to obtain a steel matrix;

[0087] S41. Perform continuous hot-dip galvanizing annealing on the steel substrate to obtain hot-dip galvanized high-strength steel. The process parameters of the continuous hot-dip galvanizing annealing are shown in Table 2.

[0088] Table 2 Process parameters of continuous hot-dip galvanizing annealing

[0089]

[0090]

[0091] The hot-dip galvanized high-strength steel obtained in the embodiment and the comparative example was subjected to mechanical property tests. The mechanical properties and retained austenite content of the hot-dip galvanized high-strength steel are shown in Table 3.

[0092] Table 3 Mechanical properties and retained austenite content of hot-dip galvanized high-strength steel

[0093]

[0094] It can be seen from Tables 1 to 3 that the chemical composition and annealing process of Example 1 are both within the required range of the present invention, the yield and tensile strengths meet the requirements, the elongation is greater than 13%, and the hole expansion rate is good; Comparative Example 1 has a high tensile strength due to excessively high C content, and the elongation is lower than 13%; Comparative Example 2 and Comparative Example 3 have a tensile strength lower than 1180MPa due to low C content and low Mn content, respectively; Comparative Example 4 has a low Si content, resulting in low Mn content and elongation; Comparative Example 5 does not contain Nb, resulting in yield and tensile strengths close to the lower limit, and the hole expansion rate is not high; Comparative Example 6 does not contain Ti, and its effect is close to that of Comparative Example 5; Comparative Example 7 has a low elongation due to a soaking temperature lower than 750°C; Comparative Example 8 has a high yield strength ratio and an elongation lower than 13% due to a rapid cooling temperature lower than 150°C; Comparative Example 9 has a low tensile strength and elongation due to a soaking temperature that is too high. By comparing Example 1 with Comparative Examples 5 and 6, it can be seen that although the lack of Nb and Ti has little effect on the elongation, it has a certain effect on the strength and hole expansion rate.

[0095] Figure 2 The microstructure of the 1180MPa grade hot-dip galvanized high-strength steel provided in Example 1 of the present application, Figure 3 The typical microstructure of the conventional 1180MPa grade hot-dip galvanized dual-phase steel provided in this application. Figure 2 and Figure 3By comparison, it can be seen that the microstructure of Example 1 is composed of lath martensite and a small amount of ferrite and para-A, with the para-A content of more than 10%; while the traditional 1180MPa grade bidirectional steel is mainly composed of equiaxed martensite, ferrite and bainite. Since the para-A content in Example 1 is as high as 15%, and the hard phase is in lath form, it can effectively resist the initiation and expansion of cracks, so the mechanical properties are excellent.

[0096] In addition, one or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0097] In the embodiment of the present invention, the high-strength steel does not add expensive alloy elements such as Mo, and does not need to be cold-rolled, so the production cost is lower.

[0098] In the embodiment of the present invention, the yield strength of the prepared hot-dip galvanized high-strength steel is ≥850 MPa, the tensile strength is ≥1180 MPa, the elongation A80 is ≥13%, and the hole expansion rate is ≥32%.

[0099] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A 1180MPa grade hot-dip galvanized high-strength steel, characterized in that: The hot-dip galvanized high-strength steel comprises a steel substrate and a galvanized layer attached to at least a portion of the surface of the steel substrate. The chemical composition of the steel substrate comprises, by mass fraction: C: 0.23% to 0.28%, Si: 1.0% to 1.9%, Mn: 2.3% to 2.8%, Al>0 and ≤0.1%, P≤0.02%, S≤0.01%, Nb>0 and ≤0.04%, Ti>0 and ≤0.04%, and the remainder is Fe and unavoidable impurities; Measured by volume fraction, the microstructure of the steel matrix includes: ferrite: 10% to 30%, martensite: 75% to 85%, and retained austenite: 9% to 18%.

2. The hot-dip galvanized high-strength steel according to claim 1, characterized in that: The microstructures of the ferrite, martensite and retained austenite are all lath-shaped.

3. The hot-dip galvanized high-strength steel according to claim 2, characterized in that: The average grain size of the ferrite is ≤3 μm, the average grain size of the martensite is ≤1.5 μm, and the average grain size of the retained austenite is ≤0.8 μm.

4. The hot-dip galvanized high-strength steel according to claim 1, characterized in that: Calculated by mass fraction, the chemical composition of the steel matrix includes: C: 0.24% to 0.26%, Si: 1.4% to 1.7%, Mn: 2.4% to 2.6%, Nb: 0.01% to 0.03%, and Ti: 0.01% to 0.03%.

5. The hot-dip galvanized high-strength steel according to claim 1, characterized in that: The hot-dip galvanized high-strength steel meets at least one of the following properties: yield strength ≥ 850MPa, tensile strength ≥ 1180MPa, elongation A 80 ≥13%, hole expansion rate ≥32%.

6. A method for preparing hot-dip galvanized high-strength steel according to any one of claims 1 to 5, characterized in that: The method comprises: Obtaining a casting billet having the chemical composition; The ingot is heated, rolled, cooled and coiled in sequence to obtain a hot-rolled plate; the coiling temperature is ≤300°C; The hot-rolled plate is subjected to surface treatment to obtain a steel matrix; The steel substrate is subjected to continuous hot-dip galvanizing annealing to obtain hot-dip galvanized high-strength steel.

7. The method according to claim 6, characterized in that The method of subjecting the steel substrate to continuous hot-dip galvanizing annealing to obtain hot-dip galvanized high-strength steel comprises: The steel substrate is subjected to a soaking treatment at a temperature of 750° C. to 850° C.; Slowly cooling the steel substrate after the soaking treatment; the slow cooling temperature is 650° C. to 720° C.; The steel substrate is rapidly cooled after slow cooling; the rapid cooling temperature is 150° C. to 250° C.; Performing aging treatment on the steel matrix after rapid cooling; The steel substrate after aging treatment is hot-dip galvanized to obtain hot-dip galvanized high-strength steel.

8. The method according to claim 7, characterized in that The temperature of the aging treatment is 200° C. to 350° C., and the time of the aging treatment is 0.5 min to 1 min.

9. The method according to claim 7, characterized in that: The hot dip coating temperature is 440° C. to 460° C., and the hot dip coating belt speed is 70 mpm to 100 mpm.

10. The method according to claim 6, characterized in that The heating temperature is 1150°C to 1250°C; and / or the final rolling temperature is 870°C to 930°C; and / or the coiling temperature is 200°C to 300°C.